Age, growth and mortality in the giant snail Adelomelon beckii (Broderip 1836) on the Argentinean shelf - Arrighetti, Florencia (2011)
The marine subtidal volutid snail Adelomelon beckii was studied in order to obtain their population dynamics, particularly on growth, age, mortality and production. Stable oxygen isotope ratios confirmed semiannual formation of internal growth marks. A von Bertalanffy growth model fitted 308 size-at-age data pairs. A. beckii potential lifespan in Mar del Plata (Argentina) region is 29years, being rather long lived compared to other large gastropods. Total mortality Z and natural mortality M were calculated to be 0.210y-1 and 0.081y-1 respectively. Fishing mortality F amounts to 0.129y-1 corresponding to an exploitation rate E of 0.614, a value much beyond the optimum rate of 0.427. The current exploitation regime will be unsustainable in the long run unless a proper management approach establishes.